Who is the inventor under the Patents Act 1983? - The concept of invention and inventorship / Lim Heng Gee - Lim, Heng Gee (Faculty of Administratron and Law, 2004)
In the context of patentability it may not be necessary or crucial to determine whether a particular subject matter is an invention, especially in view of the provision of a list of non-patentable inventions in the Patents Act 1983 (the Act)-1 However, a proper appreciation of the meaning of invention is important, as this will permit the determination of who the inventor of an invention is. Inventorship is also crucial in disputes between an inventor and someone who has allegedly stolen the inventive concept from him to gain a patent. Further, in the case of employee inventions which belong to the employer under the Act, an employee is entitled to equitable remuneration, over and above his normal salary for his contribution to the increased wealth of his employer.2 The employee who is claiming to be so entitled would have to justify his claim by proving some recognised contribution to the invention.